Pollution in a promised land : an environmental history of Israel - Tal, Alon, 1960- (University of California Press, 2002)
Virtually undeveloped one hundred years ago, Israel, the promised "land of milk and honey," is in ecological disarray. In this gripping book, Alon Tal provides--for the first time ever--a history of environmentalism in Israel, interviewing hundreds of experts and activists who have made it their mission to keep the country's remarkable development sustainable amid a century of political and cultural turmoil